2019
DOI: 10.1186/s13756-019-0575-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a PCR point of care test for influenza A/B on an acute medical unit in a large UK teaching hospital: results of an observational, pre and post intervention study

Abstract: Background Influenza viruses is a leading cause of acute respiratory infection, placing a significant burden on healthcare. To reduce hospital transmission, patients clinically suspected of having influenza are isolated and offered empirical antiviral treatment. Here we report the use of a point of care test (POCT) for influenza viruses in an acute medical unit (AMU) at Queen Elizabeth Hospital Birmingham for patients presenting with influenza-like illness. Methods A PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…CLIAwaived means that these tests can be performed outside of a laboratory and by non-laboratory staff such as nurses. Studies of these platforms have shown clinical impact for influenza detection in both the inpatient and ambulatory settings [53,54]. In a prospective, single-season study of urgent care centers connected to their health system, Benirschke et al found a significant reduction in the use of antibiotics for those who tested positive for influenza by a POC molecular test compared to those who tested positive by a POC antigen test [54].…”
Section: Point-of-care Molecularmentioning
confidence: 99%
“…CLIAwaived means that these tests can be performed outside of a laboratory and by non-laboratory staff such as nurses. Studies of these platforms have shown clinical impact for influenza detection in both the inpatient and ambulatory settings [53,54]. In a prospective, single-season study of urgent care centers connected to their health system, Benirschke et al found a significant reduction in the use of antibiotics for those who tested positive for influenza by a POC molecular test compared to those who tested positive by a POC antigen test [54].…”
Section: Point-of-care Molecularmentioning
confidence: 99%
“…However, in the viral influenza group, 7 studies 3,4,11,14,19,20,22 showed a significant decrease in ED-LOS, with 4 showing no significant change in ED-LOS. 6,12,18,21 The remaining 10 studies 5,[7][8][9][10]13,[15][16][17]23 did not report any findings related to ED-LOS.…”
Section: Resultsmentioning
confidence: 99%
“…Among paediatric patients, the use of rapid tests demonstrated a decrease in emergency department length of stay, a reduction in further diagnostic tests, and an increase in the appropriate use of antibiotics and antivirals [5]. Similarly, a more appropriate use of oseltamivir, shorter time to isolation, and a reduction in length of stay were also shown among adults [6]. Nevertheless, considering the methodological limitations, we believe that the conclusions driven by the post hoc analysis of the ResPOC study regarding the impact of turnaround time on antibiotic use and length of stay should be interpreted with caution [7].…”
mentioning
confidence: 94%